"One country, two systems": the end of a legitimating ideology?. Issue 2 (3rd April 2017) - Scott, Ian
Abstract : "One country, two systems" is the formula under which Hong Kong reverted to Chinese sovereignty in 1997. Embodied in Hong Kong's Basic Law, it formally provides for an unchanged system and a high degree of autonomy in most matters other than defence and foreign affairs. Since the Hong Kong people did not expressly consent to the reversion to Chinese sovereignty, "one country, two systems" became de facto a legitimating ideology. However, it is interpreted in very different ways. The Chinese government sees it as a policy designed to integrate Hong Kong into China. For many Hong Kong people, it is a contract guaranteeing a high degree of legislative and executive autonomy, judicial independence and the rule of law, civil liberties, and progress towards a more democratic system. This article explores the tensions arising from these different perspectives.